Reconstructing paleotrophic relationships on the Brazilian Romualdo Formation (Lower Cretaceous) through mercury analysis in fossils - Antonietto, Lucas Silveira; Hamid, Igor; Holgado, Borja; Rocha, Antonio Leite; Ferreira, Maria Andréia; Saraiva, Antônio Álamo Feitosa; Lacerda, Luiz Drude de; Silva, Rafael Costa da (Frontiers in Earth Science, 2025)
Mercury (Hg) biomagnification values tend to reflect relationships between species in the trophic web, where larger values indicate higher positions in the web. Herein, we present a pioneering attempt to reconstruct the paleotrophic linkages during the onset of the Romualdo Formation in the Araripe Basin (northeastern Brazil) based on analyses of the Hg concentrations ([Hg]) in fossil specimens recorded in this lithological unit. To understand these relationships, several vertebrate taxa were analyzed through cold vapor generation atomic absorption spectrometry (CV-AAS) to quantify [Hg] in both fossils ([Hg]Fossil) and their surrounding concretions ([Hg]Rock). The observed ratios (log[Hg]Sample) indicate greater biomagnification with changes in the feeding habits and sizes of the evaluated vertebrate taxa; the lowest values were observed in the small actinopterygian fish genera Rhacolepis and Tharrhias while the peak values were noted in large predators like Cladocyclus and Calamopleurus (apex species of the trophic pyramid). The feeding habits of Vinctifer were also reviewed, and the genus was reinterpreted from a filter feeder to a mesopredator; Neoproscinetes and an unidentified batoid ray (Chondrichthyes) were two durophagous bottom-feeding taxa that showed values compatible with their predicted feeding habits. Low values of the log[Hg]Sample ratios were observed in the ornithocheiraean pterosaurs (Reptilia), suggesting these were mesopredators specializing in smaller fish species, while Thalassodrominae presented intermediate-to-high log[Hg]Sample values, indicating their unique trophic role as terrestrial opportunistic generalists, ranging from predators to scavengers.